Den Europæiske Union: Supranationalt demokrati eller international konsolideringsstat? - Frøslee Ibsen, Malte (Politik, 2016)
This article discusses the recent debate between Jürgen Habermas and Wolfgang Streeck on the relationship between capitalism and democracy in Europe. The article recounts Streeck’s analysis of the financial crisis, the transformation of the tax state into the debt state, and the development of the EU towards an international consolidation state, which informs Streeck’s call for a retreat from Europe to the nation-state as the last line of defense against neoliberal capitalism. The article proceeds to sketch Habermas’s criticism of Streeck’s argument, and it illustrates how Habermas’ proposal for a reconstitution of the EU as a supranational democracy is motivated by foundational concerns in his critical theory of society. Finally, the article argues that the debate results in an unresolved dilemma: while only a democratized EU can reestablish the supremacy of politics over globalized markets, the EU is more likely to become further entrenched as an international consolidation state.